It's not just cricket – the portfolios of the English/Welsh cricket teams. Issue 1 (14th March 2016) - Pritchard, Adrian
Abstract : Purpose: – The purpose of this paper is to examine the range of products and services offered by the professional cricket teams in the UK. To what extent have they added to their core activity of staging matches? Design/methodology/approach: – A case study approach was adopted using both quantitative and qualitative methods. The accounts of the 18 teams and the governing body were reviewed to analyse the flow of income within the sport and categorize its sources. Interviews were then held with senior commercial staff of 12 of the teams. Findings: – All of the teams had engaged in brand extensions, offering a category of products/services that were more concerned with facilities utilization. These were not aimed at fans of the teams, as with conventional sporting extensions, but at a different market. Though there was some overlap between customers. The use of alliances and joint ventures was common in the provision of these lines. Research limitations/implications: – The research is limited to a single sport, with the portfolio being investigated from a management as opposed to a consumer perspective. The findings are likely to be relevant to other sports teams, particularly small and medium-sized enterprises, where income from the sport alone is insufficient to maintain professional status. Originality/value: – This paper adds to the previous research on typologies of brand extensions in sport by incorporating product/service lines that were aimed at resource utilization and different markets.